2021
DOI: 10.1016/j.eucr.2021.101688
|View full text |Cite
|
Sign up to set email alerts
|

Robotic radical nephroureterectomy in a patient with situs inversus totalis

Abstract: Situs inversus totalis is a rare anatomical variant in which all major organs and blood vessels are mirrored from left to right. We present a case of upper tract urothelial carcinoma in a patient with situs inversus who underwent robotic-assisted laparoscopic nephroureterectomy. We utilized conventional surgical approaches and a successful oncologic outcome was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“… 2 For robotic surgery, Britt et al reported a successful operation of robotic nephroureterectomy with SIT. 3 In general, for SIT patients, it is essential to confirm the anatomical landmark in unusual localization, such as the liver, spleen, gonadal vein, and IVC. With the laparoscopic approach, it may become more difficult by the limited operation field of the laparoscopic view.…”
Section: Discussionmentioning
confidence: 99%
“… 2 For robotic surgery, Britt et al reported a successful operation of robotic nephroureterectomy with SIT. 3 In general, for SIT patients, it is essential to confirm the anatomical landmark in unusual localization, such as the liver, spleen, gonadal vein, and IVC. With the laparoscopic approach, it may become more difficult by the limited operation field of the laparoscopic view.…”
Section: Discussionmentioning
confidence: 99%
“…The use of such a technique showed promising results in reducing postoperative pain, perioperative morbidity, and early return to work [ 18 ]. Britt et al reported the first nephrectomy to be performed using robotic techniques in patients with SIT and the third to use a minimally-invasive approach, with equivalent outcomes to conventional surgical methods [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other surgical procedures have been reported in SIT patients. These include sleeve gastrectomy for morbid obesity, 100,101 proximal gastric resection, 102 "distal" gastric resection, 103,104 total gastrectomy for malignancy, 105,106 laparoscopic pancreato-duodenectomy, 107 nephrectomy, 108 complicated choledochal cyst 109 and different colorectal operations, eg, sigmoid resection, rectal resection, etc. 110,111 We previously published a case of malignant masquerade biliary stricture in a situs inversus totalis patient (who gave his written consent to that) when distal resection of the common bile duct, cholecystectomy and hilar lymphadenectomy were performed.…”
Section: Other Operationsmentioning
confidence: 99%